Analysis of Arabic Textbooks by H. Darsono and T. Ibrahim Based on Mackey's Theory | Tahlīl Al-Kitāb Al-Madrasī Ta’līf H. Darsono Wa T. Ibrahim Li Ta’līm Al-Lughah Al-‘Arabiyyah ‘Alā Nadzariyah Mackey’s - Wahyudi, Dedi; Gina, Anisa Rahmi (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2023)
Changes in the curriculum certainly have their effects, one of which is the use of textbooks used in education. Textbooks are one of the essential elements in learning because they are learning materials and sources of guidance in them. There are many written textbooks based on the 2013 curriculum, and among the textbooks that are widely used in schools are Arabic books by H. Darsono and T. Ibrahim for grade VIII in Tsanawiyah. This study aimed to determine the selection of material, its arrangement, presentation, and repetition in Arabic textbooks for grade VIII in Madrasah Tsanawiyah according to the 2013 curriculum. The research method used in this study is the analytical descriptive method. The type of data used is qualitative data because the source of data in this study is a textbook written by H.  Darsono and T. Ibrahim to teach Arabic until eighth grade in Islamic High School. The study results are 1) Selection of subjects in textbooks written by H. Darsono and T. Ibrahim to teach Arabic for grade VIII at Madrasah Tsanawiyah, according to educational objectives, student levels, and specified time. 2) The material's structure includes structural and moral grouping and the education arrangement from accessible material to complex material. 3) The presentation of articles includes discriminatory procedures and intensive procedures. 4) Repetition in this book is based on listening, speaking, reading, and writing skills.